PENURUNAN PENGUAPAN AMONIA PADA PADI SAWAH AKIBAT PEMBERIAN ZEOLIT ALAM DAN PUPUK UREA TABLET REDUCTION OF AMMONIA VOLATILIZATION IN RICE CAUSED BY ADDING NATURAL ZEOLITE AND PRILLED UREA FERTILIZER - , Kharisun (Pembangunan Pedesaan, 2005)
The research was aimed at investigating the effect of natural zeolite of Tasikmalayan deposit and urea fertilizer on ammonia volatilization, fertilizer usage efficiency, and rice yield. This research was a pot experiment using Eutrudept soil type conducted in a glass house. The experiment was factorially arranged in a randomized block design. The factors tested were level of natural zeolite (0, 1000, and 2000 kg/ha) and urea fertilizer (0, 100, and 200 kg N prilled urea/ha and 0, 100, and 200 kg N supergranule urea/ha). Ammonia emitted was determined using Sulfuric Acid Entrapment System. Application of natural zeolite reduced volatilized N by 46%, from 78.78 mg N/pot to 42.11 mg N/pot. The highest volatilized N was observed at the application of prilled urea at 200 kg N/ha (197.23 mg/pot).